Ultrasonographic Detected Adrenomegaly in Clinically Ill Cats: A Retrospective Study - Oliveira, João; Dias, Maria Joana; Fontes, Ana Paula; Englar, Ryane E; Vicente, Gonçalo; Ferreira, Rui Lemos; Galac, Sara; Leal, Rodolfo Oliveira (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This retrospective study aimed to assess the prevalence of ultrasonographic detected adrenomegaly in clinically ill cats, evaluating the final established diagnosis, describe adrenal ultrasound findings and if the adrenomegaly was suspected or incidental. Abdominal ultrasonography reports of cats presenting to a veterinary teaching hospital between October 2018 and February 2021 were retrospectively reviewed. Cats showing adrenomegaly (one or both glands having a dorsoventral axis >4.8 mm) were selected and medical records respectively evaluated. Nine-hundred and eighty-three ultrasonographical reports were selected, of which, 68 (7%) disclosed adrenomegaly. European/Domestic Short-Hair (62/68; 91%) male (44/68; 65%) castrated (35/44; 80%) cats were overrepresented. Adrenomegaly was an incidental finding in 62/68 (91%) cats while in 6/68 (9%) it was identified in the context of investigating a potential adrenal disease. Concerning established diagnosis, chronic kidney disease was overrepresented (25/68; 37%), followed by endocrinopathies (20/68; 29%). Adrenomegaly was bilateral in 53% (36/68) of cases. In unilateral cases (32/68; 47%), it was more prevalent on the left side (23/32; 72%), with a normal-sized contralateral adrenal gland. Left adrenal demonstrated a larger size and a tendency to oval shape. This study assesses the prevalence of adrenomegaly in clinically ill cats, reinforcing it can be an incidental ultrasound finding.
Keywords: adrenomegaly; ultrasound; cats; clinically ill; endocrine